Henoch scholein purpura presenting as distal ileitis in a postmenopausal woman: A rare case report - SG Ramya; SK Nelliappa Ganesan; SN Meenakshi Sundari; V Sundaravadivelu; P Priyadharshini (International Journal of Medical Research and Review, 2016)
Henoch Schonlein purpura (HSP) is a small vessel vasculitis leading to deposition of immune IgA complexes. It presents with a tetrad of symptoms, including a purpuric rash occurring on the lower extremities, gastro intestinal involvement, renal involvement and arthritis. HSP is self limited and primarily affects children .The etiology is unknown. Treatment is mainly supportive therapy with analgesics and in severe cases, steroids are used. Here we report a rare case of Henoch Scholein purpura in a postmenopausal woman presenting as acute distal ileitis.